Customer experience for dummies - Barnes, Roy (John Wiley & Sons, 2015)
A positive customer experience is absolutely essential to keeping your business relevant. Today's business owners need to know how to connect and engage with their customers through a variety of different channels, including online reviews and word of mouth. Customer Experience For Dummies helps you listen to your customers and offers friendly, practical, and easy-to-implement solutions for incorporating customer engagement into your business plans and keep the crowds singing your praises.